The Immune Receptor Roq1 Confers Resistance to the Bacterial Pathogens Xanthomonas, Pseudomonas syringae, and Ralstonia in Tomato - Thomas, Nicholas C.; Hendrich, Connor G.; Gill, Upinder S.; Allen, Caitilyn; Hutton, Samuel F.; Schultink, Alex (Frontiers in Plant Science, 2020)
Xanthomonas species, Pseudomonas syringae and Ralstonia solanacearum are bacterial plant pathogens that cause significant yield loss in many crop species. Generating disease-resistant crop varieties provides a more durable, sustainable solution to control yield loss in place of current chemical methods that are becoming ineffective. Plant immune receptors encoded by nucleotide‐binding, leucine‐rich repeat (NLR) genes typically confer resistance to pathogens that produce a cognate elicitor, often an effector protein secreted by the pathogen to promote virulence. The diverse sequence and presence / absence variation of pathogen effector proteins within and between pathogen species usually limits the utility of a single NLR gene to protecting a plant from a single pathogen species or particular strains. The NLR protein Recognition of XopQ 1 (Roq1) was recently identified from the plant Nicotiana benthamiana and mediates perception of the effector proteins XopQ and HopQ1 from Xanthomonas and P. syringae respectively. Unlike most recognized effectors, alleles of XopQ/HopQ1 are highly conserved and present in most plant pathogenic strains of Xanthomonas and P. syringae. A homolog of XopQ/HopQ1, named RipB, is present in most R. solanacearum strains. We found that Roq1 confers immunity to Xanthomonas, P. syringae, and R. solanacearum when expressed in tomato. Strong resistance to Xanthomonas perforans was observed in three seasons of field trials with both natural and artificial inoculation. The Roq1 gene can therefore be used to provide safe, economical and effective control of these pathogens in tomato and other crop species and reduce or eliminate the need for traditional chemical controls.